2008
DOI: 10.1007/s00277-008-0495-7
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic analysis of Hb S for the diagnosis of various sickle cell disorders in Pakistan

Abstract: Sickle cell disease remains a relatively obscure theme in research on haemoglobinopathies in Pakistan. Limited data is available regarding its prevalence in the country. The objective of our study was not only to estimate the frequency of different sickle cell diseases but also to provide quantitative estimation of haemoglobin S and other haemoglobin variants using an automated high-performance liquid chromatography (HPLC) system. For this purpose, we retrospectively evaluated the results of HPLC performed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Hemoglobin S had been reported from this region [23] and the occurrence of this combination was no surprise. However, HbE and F levels did not correspond to the previously published reports in the similar condition.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Hemoglobin S had been reported from this region [23] and the occurrence of this combination was no surprise. However, HbE and F levels did not correspond to the previously published reports in the similar condition.…”
Section: Discussionmentioning
confidence: 93%
“…However, HbE and F levels did not correspond to the previously published reports in the similar condition. We hypothesized that co-existing iron deficiency reduced the quantity of HbE and high HbF in sickle cell disorders is not atypical for this geographical region [23]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic carriers of Sickle Cell Anemia comprise about 3% of the total world's population, as mentioned by the World Health Organization 2 . The Sickle Cell Anemia affected about 100, 000 people of the United States, among them 2 million are carrier 3 however, embarked decline in the mortality 4 and the mean age of death in male is 53 years and in female about 58 years 5 . In Pakistan, 0.5-1% of populationis carriers of Hemoglobin S 6 , whereas about 5.1% of prevalence found in Karachi 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Sickle Cell Syndrome : Hashmi et al [28] reported mean age at diagnosis to be 13 years in sickle cell trait cases. As in our cases, Mohanty et al [29] also reported reduced MCV and MCH in sickle cell trait cases(63.5 fl and 19.8 pg).…”
Section: Hbementioning
confidence: 99%